PENINGKATAN KEAKTIFAN BELAJAR SISWA MELALUI MODEL PEMBELAJARAN TEAMS GAMES TOURNAMENT (TGT) BAGI SISWA KELAS VI SD NEGERI KOTAGEDE 3 - Widyastuti, Nur Sri; Suprapti, Suprapti (Universitas Sarjanawiyata Tamansiswa, 2021)
The purpose of this study was to increase student learning activeness in thematic social studies learning by using the Team Game Tournament (TGT) learning model in class VI B SD Negeri Kotagede 3. The focus of this study was to increase student learning activeness in social studies learning. This research is a Classroom Action Research (CAR), which follows the stages of the Kemmis and Taggart Model. The research subjects were all students of class VI B SD N Kotagede 3 in the 2019/2020 academic year which consisted of 30 students. The data collection techniques used were observation, field notes, and questionnaires. The criterion for the success of this study is measured by the amount of student activeness with a minimum percentage acquisition of 70%. The results showed that the TGT learning model could increase student learning in social studies learning. This is evidenced by an increase in negativity from 50% before the action to 60% with an increase of 10%. Whereas in cycle 1 to cycle 2 there was an increase of 17% to 77%.